2021
DOI: 10.1038/s41598-021-85673-w
|View full text |Cite
|
Sign up to set email alerts
|

Radical pairs may play a role in xenon-induced general anesthesia

Abstract: Understanding the mechanisms underlying general anesthesia would be a key step towards understanding consciousness. The process of xenon-induced general anesthesia has been shown to involve electron transfer, and the potency of xenon as a general anesthetic exhibits isotopic dependence. We propose that these observations can be explained by a mechanism in which the xenon nuclear spin influences the recombination dynamics of a naturally occurring radical pair of electrons. We develop a simple model inspired by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 54 publications
9
73
0
Order By: Relevance
“…In summary, our results suggest that quantum entanglement might lie behind the mechanism of lithium treatment for BD, similarly to magnetoreception in animals 33 and (as recently proposed) xenon-induced anesthesia 35 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In summary, our results suggest that quantum entanglement might lie behind the mechanism of lithium treatment for BD, similarly to magnetoreception in animals 33 and (as recently proposed) xenon-induced anesthesia 35 .…”
Section: Discussionsupporting
confidence: 81%
“…In this highly speculative context, entangled RPs could play crucial roles as sources of entanglement, and the present work could be viewed as another piece of evidence consistent with this idea in addition to Ref. 35 . In particular, superoxide radicals can give rise to singlet oxygen, which can emit photons 99 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The authors concluded that the presence of CRY is critical in axon outgrowth under low-intensity repetitive transcranial magnetic stimulation (rTMS). It has also been suggested that RP may help explain xenon-induced anesthesia [67] and the lithium effects on mania [39]. It, therefore, seems RPs could play critical roles in the functionalities of the brain in general and the CC in particular.…”
Section: Introductionmentioning
confidence: 99%